Nice Guys Finish Last: Do Honest Taxpayers Face Higher Tax Rates?. (February 2014) - Doerrenberg, Philipp; Duncan, Denvil; Fuest, Clemens; Peichl, Andreas
Summary This paper examines the relationship between 'tax morale' and tax policy. Using a unique cross‐country data set based on the World Values Survey and the World Tax Indicators, we find that income groups with high tax morale face higher average and marginal tax rates. We propose three possible mechanisms which could help to explain our results: i) an inverse elasticity argument where governments seek to minimize distortions, ii) a political economy argument where governments take voting behavior into account, and iii) an administrative costs argument where taxing high morale groups is more cost efficient.